2019
DOI: 10.30958/aje.6-2-3
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Teachers' Perceptions of Emotional Labor and Teacher Burnout and Teachers' Educational Level

Abstract: use of the specific emotional labor techniques (surface, deep or natural acting). The conclusion of this study is that various variables can influence teachers' use of techniques associated with emotional labor. Changes in such variables, such as teachers' level of burnout and level of education, may improve management of emotions in teaching and improve their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Nevertheless, whether burnout is the result of emotional labor or burned-out employees start to employ surface acting responses as they lack the resources to apply more genuine and empathetic strategies (i.e., deep and natural acting) is not yet well understood. Few studies have examined burnout as the cause of emotional labor [ 8 , 15 , 36 ], and those that did have shown that burnout leads to greater surface acting strategies and emotional labor. This association is consistent among the studies, suggesting that when emotional exhaustion and fatigue rises, surface acting rises too [ 16 , 33 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, whether burnout is the result of emotional labor or burned-out employees start to employ surface acting responses as they lack the resources to apply more genuine and empathetic strategies (i.e., deep and natural acting) is not yet well understood. Few studies have examined burnout as the cause of emotional labor [ 8 , 15 , 36 ], and those that did have shown that burnout leads to greater surface acting strategies and emotional labor. This association is consistent among the studies, suggesting that when emotional exhaustion and fatigue rises, surface acting rises too [ 16 , 33 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the studies that examined burnout as a predictor of emotional labor, they indicate that greater exhaustion scores predict emotional labor [ 8 ]. Correspondingly, further studies also show that higher burnout levels are related to higher surface acting while lower burnout levels are related to NFE; no associations were observed between burnout and deep acting [ 15 , 36 ].…”
Section: Summary Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional labor is centrally located in teaching performance (Yin, 2015). The emotional labor of teachers stems from the nature of the work they perform and plays an important role in increasing the performance of teachers (Zaretsky and Katz, 2019). Teaching satisfaction is remarkably related to emotional labor of teachers (Huang, Yin and Han, 2019).…”
Section: The Effect Of Accountability On Occupational Awareness With the Mediating Roles Of Contribution To Organization Emotional Labor mentioning
confidence: 99%
“…Educators are expected to have an ability to place their emotional, physical, and mental aspects within sets of compartments inside their heads and deals with their afflictions in the right time and place, gaining perspective on how their problems should be dealt with later on (Rozuel, 2009). After all, teachers are confronted with an emotional scene in the classroom (Zaretsky & Katz, 2019) because they are dealing with students having diverse personalities and behavior.…”
Section: Introductionmentioning
confidence: 99%